Arles du xve au xvie siècle, entre latin, provençal et français : deux siècles d’histoire, trois langues en contact - Marie Rose Bonnet (Revue des Langues Romanes)
The city of Arles, for many reasons, soon became accustomed to writing evidence of relations with the different powers that governed it. Since the thirteenth century, the Counts of Anjou have succeeded each other at the head of Provence and Arles was then confronted with the representative of the count, the archbishop and the consuls elected by the Arlésiens. The fifteenth and sixteenth centuries reflect this situation in their linguistic and scriptural diversity. Three linguistic systems then appear in the documents, Latin, Provençal, and finally French, when Provence becomes French and Arles adjacent land. Alternation, rather than diglossia, will then mark, at first, these texts. The initial Latin/Provencal bilingualism is thus gradually replaced by Provencal/French bilingualism, which then gives way to a French monolingualism, tainted by Provencal despite all, trilingualism having also existed. A language, even written, reveals a lot about the society that uses it, and depends on many factors, external or internal. Languages competition makes historical vagaries and societal choices visible.